2017
DOI: 10.1007/s00604-017-2228-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine sensors development based on a glassy carbon electrode modified with a nanostructured TiO2 films by electrochemical approach

Abstract: In this work, we describe the response of a selective hydrazine sensor based on a film of TiO 2 nanoparticles faceted predominantly in 101 and 001 sides. The sensor was fabricated depositing the nanoparticles plus 5% of nafion on a glassy carbon electrode.Chemical sensing for hydrazine was performed through simple and reliable current-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 48 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Hydrazine is detected through its oxidation on suitable electrodes . Electrochemical oxidation of hydrazine at the surface of the bare electrode is kinetically sluggish .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Hydrazine is detected through its oxidation on suitable electrodes . Electrochemical oxidation of hydrazine at the surface of the bare electrode is kinetically sluggish .…”
Section: Figurementioning
confidence: 99%
“…Rahman et al reported TiO 2 films and SrO‐CNT composite based hydrazine sensor wherein ethanolic nafion solution was used as conducting coating binder with active material during electrode fabrication. The current work is advantageous as it reports a high yield, green synthesis approach of CQD using a benign precursor, chia seeds where, the as‐prepared products were self‐passivated providing the CQD with excellent solubility thus avoiding the need for a separate step for passivation.…”
Section: Figurementioning
confidence: 99%
“…Therefore, a reliable technique for the detection of hydrazine (4nitrophenylhydrazine) is necessary. In recent, many kinds of research have been conducted based on CoS2-CNT nanocomposites [26], SrO.CNT NCs [27], Fe2O3 NPs [28], Co-doped ZSM-5 zeolites [25], TiO2 nanoparticles [32], Fe2O3/CeO2 nanocubes [33] and ZnO nano-urchins [29] coated on GCE for precious hydrazines detection ( both aromatic and aliphatic) applying electrochemical (I-V) approach. This experimental work performed to assemble a sensor in I-V approach selective to 4-NPHyd with ZnO/SnO2 NPs coated on GCE.…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue was inserted into the nanogold/mesoporous carbon nitride composites for selective and sensitive Pb 2+ detection . Various modified functional carbon materials composite material are used to selective detection of different heavy metal ions by using optical, differential pulse voltammetry, anodic stripping, electrical, colorometric, adsorption‐desorption, chronoamperometric, and I−V methods . Based on previous observation, it is of great interest to study the P(Py‐co‐OT)/CF NCs for sensor applications.…”
Section: Introductionmentioning
confidence: 99%